CH4 accumulation characteristics and relationship with deep CO2 fluid in Lishui sag, East China Sea Basin. (April 2020) - Huang, Yahao; Tarantola, Alexandre; Lu, Wanjun; Caumon, Marie-Camille; He, Sheng; Zhuang, Xinguo; Yan, Detian; Pironon, Jacques; Wang, Wenjing
Abstract: Co-accumulation of carbon dioxide and hydrocarbon gas is common and widely existing in oil and gas basins. Such two natural pools are located in Lishui sag (East China Sea Shelf Basin), as a favorable prospecting area for exploration. CO2 gas derived from inorganic mantle sources and CO2 accumulation times have been investigated. In this study, petrographic observation shows pure CH4, CH4 -rich, H2 O-rich and hybrid CH4 -CO2 fluid inclusions exist in healed micro-fractures and overgrowths of quartz mineral in Palaeocene reservoirs of Lishui sag. The pressure–temperature–time–composition ( PVT – x ) properties of CH4 -bearing inclusions were obtained by Raman quantitative analysis and thermodynamic models. These results provide important constraints on the P-T entrapment conditions and predict relative accumulation time of CH4 fluid. Combination of carbon isotope analyses, inclusion petrography, microthermometry, PT entrapment conditions of CH4 -bearing inclusions, hydrocarbon generation and simulation of burial history permit to assign periods of CH4 fluid activity and its sequence with CO2 fluid. Methane charging time occurs during two stages in LS-A: low density CH4 fluid (~0.10 g/cm 3 or lower) were trapped during late Oligocene (30-20 Ma) and high density (>0.115 g/cm 3 ) during a Pliocene (8-1 Ma) CH4 accumulation event. CO2 fluid accumulation (Miocene, 21-4 Ma) displaced the methane gas trapped in the early stage. Pliocene CH4 fluid partial displaced Miocene CO2 fluid. In well B, only high density (0.144–0.153 g/cm 3 ) recorded a late Oligocene to early Miocene (36-19 Ma) CH4 accumulation event, Pliocene (5-3 Ma) CO2 fluid displaced early CH4 fluid. Micro-thermometry, composition of fluid inclusion, features of reservoir, thermal maturity reflect hydrothermal fluid vertical migration and the existence of Supercritical CO2 extraction. Highlights: Hydrocarbon stable isotope show crude oil associated gas generation. Petrography, micro-thermometry and Raman method discriminate the type of inclusion. PVT-x properties of CH4 -bearing inclusions were determined by Raman quantification. Analysis of CH4 accumulation time and displacement relationship with CO2 fluid.